Assessment of Novel Stability-Indicating Technique-based HPLC Approach for One Genotoxic Impurity and Three Related Substance Impurities of Lurasidone Hydrochloride: Degradation Studies on Lurasidone Hydrochloride - Ramanjaneyulu, Siddabathuni; Narayana Rao, K.M.V.; Pulipaka, Shyamala (Asian Journal of Chemistry, 2022)
The present work communicates the selective quantification of a genotoxic impurity (P-LUH) and lurasidone hydrochloride (LUH) related compounds (I1-LUH, I2-LUH and I3-LUH) as potential impurities in the LUH active therapeutic ingredient using novel stability-indicating technique-based HPLC approach. The P-LUH, I1-LUH, I2-LUH and I3-LUH were separated on column Inerstil ODS 3V having length size of 250 mm, identification value of 4.6 mm and particle dimension of 5 μm. After that, a high sensitivity PDA detector at 231 nm was used to detect the signal of impurities. The method was thoroughly validated and established to be accurate and also precise with a rectilinear concentration range of 0.01% to 0.18% for P-LUH, 0.03% to 0.18% for I1-LUH, 0.033% to 0.18% for I2-LUH, 0.031% to 0.18% for I3-LUH and 0.03% to 0.12% for LUH with regard to a 10 μL injection. The LUH sample was exposed to UV-visible light open/closed conditions, heat for 10 days, relative humidity for 10 days, 4 N HCl for 3 days, 4 N NaOH for 1 h, 6% peroxide for 7 h, Milli Q water for 88 h and to 0.05 M Cu2+ for 88 h. The LUH was satisfactorily determined in the existence of degradation products including impurities, the LUH was satisfactorily determined. The formation of P-LUH, I1-LUH, I2-LUH and I3-LUH during degradation studies on LUH was also studied. The P-LUH, I1-LUH, I2-LUH and I3-LUH were effectively determined in LUH batches and the findings indicated the use of a novel stability-indicating technique-based HPLC approach for the selective assessment of trace impurities in LUH drug substances.